Peça filme: o efeito cinema e a poética dos espetáculos teatrais de Saulo Sisnando - SISNANDO, Saulo Alexandre Picanço (Universidade Federal do Pará, 2017)
This work intends to investigate the influence of the cinema on Saulo Sisnando's plays by using projections, as in the Play-Movie popPORN - sete vidas e infinitas possibilidades de corações partidos, or considering the way the film editing was added to the staging of Cartas para Ninguém Play-Movie. This work also aims at demonstrating step by step procedures for inserting film techniques into the play o misterioso desaparecimento de Deborah Rope (built along with this work), discussing the possibility of such a hybridization, which goes beyond the use of audiovisual resources (yet using it), but seizing typically film concepts as film editing, montage, close-ups, fades, cuts, plans against plans, sequences, frameworks, etc, in a way to achieve a "film effect". Besides, it also intends to analyze the Play-Movie O misterioso desaparecimento de Deborah Rope from the dramaturgical building up into the execution on stage, when, following a realistic theory of André Bazin, it will be analyzed through the film editing and plasticity of the image prism.